Design of an Infographic based on Participatory Online Learning and its Impact on Academic Achievement and Attitudes among High School Students in Computer Subject Through the Lens of Cognitive Load Theory - حامد علي مبارك الشهراني (مجلة العلوم التربوية والنفسية, 2024)
This study aimed to identify the design of an infographic based on participatory learning through the lens of cognitive load theory and its impact on academic achievement and attitudes among high school students in the computer subject. Following a quasi-experimental approach, 53 sophomore students in high schools in Abha City were randomly selected and distributed into two groups: a control group of 26 and an experimental group of 27. The study found that using infographics in computer subject lessons has enhanced students' academic achievement and attitude. The results demonstrated a significant difference (0.05) between the experimental and control groups in the average score of the achievement test. Further, the study results revealed statistically significant differences between the students' average scores in the experimental group and the control group on the post-test mean score of attitudes toward infographics in favor of the experimental group. Implementing infographics is recommended in cases where students' academic achievement and attitudes toward computer lessons are inadequate. Keywords: Infographics, academic achievement, attitudes, participatory learning, cognitive load theory.